Influence of oncogenic transcription factors on chromatin conformation and implications in prostate cancer - Yang YA (The Application of Clinical Genetics, 2014)
Yeqing Angela Yang,1 Jung Kim,1 Jindan Yu1,21Division of Hematology/Oncology, Department of Medicine, 2Robert H Lurie Comprehensive Cancer Center, Northwestern University, Feinberg School of Medicine, Chicago, IL, USAAbstract: In recent years, facilitated by rapid technological advances, we are becoming more adept at probing the molecular processes, which take place in the nucleus, that are crucial for the hierarchical regulation and organization of chromatin architecture. With an unprecedented level of resolution, a detailed atlas of chromosomal structures (histone displacement, variants, modifications, chromosome territories, and DNA looping) and mechanisms underlying their establishment, provides invaluable insight into physiological as well as pathological phenomena. In this review, we will focus on prostate cancer, a prevalent malignancy in men worldwide, and for which a curative treatment strategy is yet to be attained. We aim to catalog the most frequently observed oncogenic alterations associated with chromatin conformation, while emphasizing the TMPRSS2-ERG fusion, which is found in more than one-half of prostate cancer patients and its functions in compromising the chromatin landscape in prostate cancer.Keywords: chromatin conformation, ERG, prostate cancer